2016
DOI: 10.7196/samj.2016.v106i4.10168
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors associated with asthma prevalence and severity among children living in low-income South African communities

Abstract: Background. Rates of asthma, poverty and social deprivation are high among young people in South Africa (SA), yet asthma interventions largely remain focused on biomedical factors. Objective. To investigate associations between socioeconomic factors and childhood asthma. Methods. We recruited 6 002 children aged 10 -17 years from six low-income urban and rural sites in three SA provinces. Self-report questionnaires measured health status, sociodemographics and socioeconomic factors. Logistic regression and med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“… 1 In this study, potential risk factors associated with allergic diseases were male gender, consuming fast food, trucks passing near houses, having a dog or cat at home, and a positive SPT for Bermuda grass or cat fur. Although part of these findings have already been described in previous studies investigating the epidemiology of asthma among children, 33 , 34 our results extend these findings to other allergic diseases.…”
Section: Discussionsupporting
confidence: 89%
“… 1 In this study, potential risk factors associated with allergic diseases were male gender, consuming fast food, trucks passing near houses, having a dog or cat at home, and a positive SPT for Bermuda grass or cat fur. Although part of these findings have already been described in previous studies investigating the epidemiology of asthma among children, 33 , 34 our results extend these findings to other allergic diseases.…”
Section: Discussionsupporting
confidence: 89%
“…[22] In another South African study using self-reported questionnaires amongst 6002 children from both rural and urban settings to investigate socioeconomic risk factors for childhood asthma, asthma severity increased with socioeconomic deprivation. [23] This association may be attributable to both the inequitable distribution of health care, poor access to diagnosis and care and environmental factors, such as increased exposure to indoor pollution and smoking. [22,23] Self-reported smoking was an important risk factor with almost 9% of participants self-reporting smoking at a relatively young age.…”
Section: Discussionmentioning
confidence: 99%
“…[23] This association may be attributable to both the inequitable distribution of health care, poor access to diagnosis and care and environmental factors, such as increased exposure to indoor pollution and smoking. [22,23] Self-reported smoking was an important risk factor with almost 9% of participants self-reporting smoking at a relatively young age. While self-reported smoking is an imperfect measure, this probably represents the lowest estimate of adolescents who are currently smoking in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Economically disadvantaged people disproportionately affected by asthma and asthma severity are often exposed to chronic psychosocial stressors. 1,2 Within the psychosocial factors, there are studies assessing the caregiver's mental health, particularly the mother's, as a predictor of asthma morbidity. [3][4][5] In this sense, maternal depressive symptoms are associated with increased number of visits to the emergency department (ED), 6,7 higher number of hospitalizations, 3,5 and worsening pulmonary function in asthmatic children.…”
Section: Introductionmentioning
confidence: 99%